A Comprehensive Review of Magnetic Nanomaterials Modern Day Theranostics - Gul, Saima; Khan, Sher Bahadar; Rehman, Inayat Ur; Khan, Murad Ali; Khan, M. I. (Frontiers in Materials, 2019)
Substances at nanoscale, commonly known as “nanomaterials,” have always grabbed the attention of researchers for hundreds of years. Among these different types of nanomaterials, magnetic nanomaterials have been the focus of considerable attention during the last two decades as evidenced by an unprecedented increase in the number of research papers focusing these materials. Iron oxide magnetic nanoparticles have occupied a vital position in imaging phenomena; as drug vehicles, controlled/sustained release phenomena and hyperthermia; atherosclerosis diagnosis; prostate cancer. In fact, these are wonderful “theranostic” agents with some under clinical trials for human use. In this review, we have attempted to highlight the advances taking place in the field of magnetic nanoparticles as theranostic agents. Extensive progress has been made in the two most important parameters, namely, control over the size and shape which decide the importance of iron oxide magnetic nanoparticles by developing suitable procedures like precipitation, co-precipitation, thermal decomposition, hydrothermal synthesis, microemulsion synthesis and plant mediated synthesis. After using a suitable synthetic route, workers encounter the most daunting task linked with the materials at nanoscale i.e., the protection against corrosion. Only properly protected iron oxide magnetic nanoparticles can be further connected to different functional systems to make building blocks for application in catalysis, biology and medicines. Finally, “theranostics” which is a combined application of imaging and drug delivery has been discussed. With all the potential uses, toxicity of the of iron oxide magnetic nanoparticles has been discussed.